Enhanced passive safety surveillance of high‐dose and standard‐dose quadrivalent inactivated split‐virion influenza vaccines in Germany and Finland during the influenza season 2021/22 - Gandhi‐Banga, Sonja; Wague, Sophie; Shrestha, Anju; Syrkina, Olga; Talanova, Oxana; Nissilä, Markku; Stuff, Karl; Monfredo, Céline (Influenza and other respiratory viruses, 2023)
Background Enhanced passive safety surveillance (EPSS) was conducted for quadrivalent inactivated split‐virion influenza vaccines (IIV4) in Germany (high dose [HD], aged ≥60 years) and in Finland (standard dose [SD], aged ≥6 months) at the beginning of the northern hemisphere 2021/22 influenza season. The primary objective was to assess adverse drug reactions (ADRs) occurring ≤7 days post‐vaccination. Methods Vaccinees were issued vaccination cards (VC) and were encouraged to report ADRs via an electronic data collection system or by telephone. ADRs were assessed by frequency, time to onset, intensity and by age group. The vaccinee reporting rate (RR) was calculated as the number of vaccinees reporting ≥1 ADR divided by total vaccinees. Reactogenicity was compared with previous experiences with each vaccine. Results Among 903 HD‐IIV4 vaccinees in Germany, 17 reported ≥1 ADR within ≤7 days post‐vaccination: RR, 1.88% (95% CI: 1.10, 3.00). Time to onset was known for 53/65 ADRs, all of which occurred ≤7 days post‐vaccination. In Germany, seven ADRs were reported that were not listed previously. Among the 1000 SD‐IIV4 vaccinees in Finland, 49 reported ≥1 ADR within ≤7 days post‐vaccination: RR, 4.90% (95% CI: 3.65, 6.43). Time to onset was known for 126/134 ADRs, of which 125 occurred ≤7 days post‐vaccination. In Finland, 21 ADRs were reported that were not listed previously. No ADRs reported during follow‐up were serious. Conclusions The EPSS for HD‐IIV4 and for SD‐IIV4 in the 2021/22 influenza season did not suggest any clinically relevant changes in safety beyond what is known/expected for IIV4s.